IMPLEMENTATION OF WORK SHEET BASED ON APOS MODEL ON INTEGRAL CALCULUS COLLEGE IN THE SUBJECT OF THE TRANSENDENT FUNCTION IN STUDY PROGRAM IN MATHEMATICS EDUCATION FKIP UNIB ACADEMIC YEAR 2017/2018 - Hanifah, Hanifah (UNIB Press, 2017)
ABSTRACTAPOS Model is a Mathematics Learning Model Based on APOS Theory, which is student-centered and has syntax with phases: Orientation, Practicum, Small Group Discussion, Class Discussion, Exercise and Evaluation. To support the APOS Model, the APOS Model Worksheet was designed. The purpose of this study was to determine the practicality and effectiveness of APOS Model Worksheets by students on the subject of Transcendent function. The research subjects were students of Mathematics Education Semester 3 Class A FKIP UNIB FY 2017/2018 totaling 37 people. Practical data on worksheets were collected through student practicality questionnaires. Effectiveness data was collected using response questionnaires, and posttest sheets. From the results of data processing obtained information: the average value of LK practicality by students = 81.94% is very practical category, the average value of student response = 84.72% is very effective category, the average value of posttest results = 68, 72% is in the effective category. From observations during learning, students were seen actively working in small groups, and each group appeared to present their work in front of the class during the class discussion phase. It can be concluded that the APOS Model-based Worksheet on the subject matter of the Transcendent Function is very practical, and effective to improve student activity, get a positive response, and average student learning outcomes are good.Keywords: APOS Model Syntax, Worksheet Based on APOS Model, Response, Learning Outcomes, Practical, and Effectiv